Differences viewpoints on child-rearing methods of chinese Americans and white americans in the United States in the 21st century = Những quan điểm khác nhau về phương pháp nuôi dạy con cái của người Mỹ gốc Hoa và người Mỹ da trắng ở nước Mỹ thế kỷ 21 - Mai, Thị Thảo (2020)
The increasing number of studies on homosexual subject underlines the fact that people are much more concerned about the issue of homosexuality which recently becomes a heated topic. The eager of the young for seeking enlightenment as well as the undeniable power of information technology and globalization helps create a more favorable condition for the homosexuals in the process of claiming for their equal rights. Therefore, the research aims at exploring the attitudes of Universtiy of Languages and International Studies students and Coe College students towards homosexuality and same-sex marriage in general, and lesbian and gay men, in particular; what are the reasons underlying not only the differences in attitude of young people toward the two targeted subjects, lesbian and gay man subject but also the dissimilarity in attitude of Vietnamese and American students toward homosexuality. Possible factors which might affect their attitude were also analyzed in order to provide a comprehensive view on the issue. The participants included 40 students coming from the two universities - University of Languages and International Studies (ULIS), Vietnam National University; and Coe College (CC), Iowa, US. While group administration questionnaire was employed in order to collect the data from ULIS students, e-mail administration questionnaire was used for CC participants. The results showed that in general, attitude of young people toward homosexuality was quite positive. However, male homosexuals were viewed slightly more negative than female ones. Attitude of CC students toward both lesbian and gay man subjects was also recorded to be less negative than of ULIS students. Besides, except for sex factor, the participants’ perceived main cause of homosexuality and the level of homosexual related movie exposure were proven to have great impact on attitude of the students.